Isolation of Prolidase from Amniotic Fluid and Study of its Kinetic and Affinity Properties Towards Pharmacological Compounds - Luay Al-Helaly (College of Education for Pure Sciences, 2019)
The research included the isolation of prolidase from human amniotic fluid using different biochemical techniques, One proteinous peak had been isolated by gel filtration using sephadex )G-50) and from sephadex (G-100) that produced by ammonium sulphate precipitation (60%) after dialysis. The approximately molecular weight of the enzyme using gel filtration chromatography (G-100) was (52269.7) Dalton and specific activity of 13516.6 unit/mg protein with 75 fold of purification. The results showed that the optimum conditions of purified enzyme from amniotic fluid were at (50 µg/ml) of protein as a source of the enzyme using (60 mM/L) Tris-HCl buffer solution at pH (8.0) act for (32) minutes at (39°C). Using Line Weaver-Burk plot, the values of maximum velocity (Vmax) and Michaelis constant (Km) were found to be (3448.2 U/L) and (10 mM/L) respectively using Gly-Pro as a substrate.  Finally, also, involved the study of the effect pharmacological chemicals compounds on the enzyme activity, the results showed that the drug chemical compounds for type ceramide, metoclopramide, pseudoephedrine, diphenhydramine-HCl, chloramphnicol, paracetamol and allopurinol give the inhibition type competitive, with increased in Km value to 66.6, 71.42, 52.63, 55.55, 83.33, 90.9 and100.0 mM/L respectively for inhibitors above, while the others pharmacological compounds for theophlline anhydrous, caffeine anhydrous, metronidazole and chlorpheniramine maleate, give the inhibition  type of non-competitive with decreased in Vmax values to 2173.9, 2439.0, 2000.0 and 2325.58 U/L respectively, but dexathamazone was an activator to the prolidase approximately 27.18 U/L.